Transarterial chemoembolization combined with apatinib with or without PD-1 inhibitors in BCLC stage C hepatocellular carcinoma: A multicenter retrospective study - Xia, Wei-Li; Zhao, Xiao-Hui; Guo, Yuan-; Cao, Guang-Shao; Wu, Gang; Fan, Wei-Jun; Yao, Quan-Jun; Xu, Shi-Jun; Guo, Chen-Yang; Hu, Hong-Tao; Li, Hai-Liang (Frontiers in Oncology, 2022)
Abstract Objective: We evaluated the efficacy and safety of transarterial chemoembolization (TACE) combined with apatinib plus PD-1 inhibitors (TACE-AP) compared with TACE combined with apatinib (TACE-A) in patients with advanced hepatocellular carcinoma (HCC) and to explore the prognostic factors affecting patient survival. Methods: Data from patients with unresectable HCC who received TACE-AP or TACE-A from December 2018 to June 2021 were collected retrospectively. The main outcome of the study was overall survival (OS) and prognostic factors affecting survival, while the secondary outcomes were progression-free survival (PFS), the objective response rate (ORR), and treatment-related adverse events (TRAEs). Propensity score matching (PSM) analysis was used to reduce patient selection bias, and the random survival forest (RF) model was employed to explore prognostic factors affecting patient survival. Results: We enrolled 216 patients, including 148 and 68 patients in the TACE-A and TACE-AP groups, respectively. A total of 59 pairs of patients were matched using PSM analysis. Before and after PSM, the OS, PFS, and ORR in the TACE-AP group were significantly higher than in the TACE-A group (before, OS: 22.5 months vs. 12.8 months, P < 0.001; PFS: 6.7 months vs. 4.3 months, P < 0.001; ORR: 63.2% vs. 34.5%, P < 0.001; after, OS: 22.5 months vs. 12.0 months, P < 0.001; PFS: 6.7 months vs. 4.3 months, P < 0.001; ORR: 62.7% vs. 30.5%, P = 0.003). Multivariate Cox regression and RF models before and after PSM analysis revealed that the main prognostic factors affecting survival were tumor number, portal vein tumor thrombus (PVTT) invasion, alpha-fetoprotein (AFP) levels, total bilirubin (TBIL) level, and treatment. There was no significant difference in TRAEs between the two groups (P > 0.05). Conclusion: Compared with TACE-A, TACE-AP significantly improved OS, PFS, and ORR in patients with advanced HCC. The number of tumors, PVTT invasion, AFP levels, TBIL level, and treatment were significant prognostic factors associated with patient survival. All observed TRAEs were mild and controllable.